MODEL OPTIMASI PENGELOLAAN INVENTARIS ASET BERBASIS WEB MENGGUNAKAN PENDEKATAN DESIGN THINKING - Ardi, Abdullah (Jurnal Teknoinfo, 2025)
Effective asset inventory management is a critical challenge for government agencies, including the Secretariat Office of Barito Kuala Regency. Inefficiencies in this process often result in inaccuracies in record-keeping, delays in reporting, and difficulties in real-time asset tracking. This study aims to develop an optimized web-based asset inventory management model by applying the Design Thinking approach to address these issues. Through the Empathize phase, it was identified that the error rate in asset record-keeping reached 25%, reporting delays extended up to 72 hours, and 35% of assets could not be tracked in real-time. In the Define phase, these issues were formulated into a need for a more accurate, efficient, and real-time accessible asset management system. The proposed solutions included the development of a web-based record-keeping system, a real-time tracking module utilizing Radio-Frequency Identification (RFID) technology, and an automated reporting feature integrated with the audit system. Testing results indicated that the new system successfully reduced record-keeping errors by 90%, shortened reporting times from 72 hours to 6 hours, and improved asset tracking efficiency by 83.3%. Users provided positive feedback, with the system achieving an average System Usability Scale score of 84.5, classified as "excellent." In conclusion, the optimized web-based asset inventory management model developed through the Design Thinking approach has proven effective in addressing key issues, enhancing efficiency, accuracy, and user satisfaction, and holds significant potential for adoption by other government agencies.